Akuntan Publik: Daya Tarik dan Faktor Pendorong Minat Mahasiswa - Fauzi, Restu Ismail; Hardiningsih, Pancawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze the influence of financial rewards, work environment, job market considerations, and artificial intelligence knowledge on accounting students' interest in choosing a public accounting career. Sampling using a convenience purpose sampling technique obtained 105 respondents. The research results show that the variables of financial rewards and labor market considerations show a significant positive influence. Students' knowledge of artificial intelligence provides significant positive results, meaning that the higher their knowledge of artificial intelligence (AI), the greater their interest in a career as a public accountant. Meanwhile, work environment variables have no effect on students' interest in pursuing a career as a public accountant, this happens because students do not prioritize risks or things gained in the work environment.